Test-retest reliability of elbow flexor contraction characteristics with tensiomyography for different elbow joint angles. (April 2019) - Latella, Christopher; Ruas, Cassio V.; Mesquita, Ricardo N.O.; Nosaka, Kazunori; Taylor, Janet L.
Abstract: Tensiomyography (TMG) has gained popularity as a tool to quantify muscle contractile properties. However, it is unclear whether joint angle and inter-stimulus interval influence the test-retest reliability of TMG. Fifteen participants (13M/2F; 29.5 ± 7.4 y) underwent TMG recording of the biceps brachii (BB) at 10°, 45° and 90° of elbow flexion with 10 and 20 s inter-stimulus rest intervals in a randomised order on two separate days. The intra-class correlation coefficient (ICC2, 1 ) and 95% confidence interval (95%CI) were calculated for delay time (Td), contraction time (Tc), sustain time (Ts), relaxation time (Tr) and maximal displacement (Dm). Additionally, the standard error of measurement (SEM), coefficient of variation (CV) and minimal detectable change (MDC) were obtained. Across conditions the ICC2, 1 varied for each parameter (Td:0.465–0.947, Tc:0.452–0.831, Ts:0.717–0.918, Tr:0.841–0.935, Dm:0.646–0.900). CV was low for Td (2.1–3.0%), Tc (4.4–7.7%) and Ts (5.5–6.9%) but greater for Tr (10.0–15.3%) and Dm (5.8–13.1%) across conditions. Ts (∼210 ms, P < 0.001) and Dm (∼17 mm, P < 0.001) were greatest at 10° and 90°, respectively, while Td was shortest (∼22.9 ms, P = 0.002) at 10° compared to other angles. No differences were observed between inter-stimulus intervals or day. The findings are expected to help shape best practice methods for TMG use in field and research based settings.